A novel framework to estimate cognitive impairment via finger interaction with digital devices. Issue 4 (28th July 2022) - Holmes, Ashley A; Tripathi, Shikha; Katz, Emily; Mondesire-Crump, Ijah; Mahajan, Rahul; Ritter, Aaron; Arroyo-Gallego, Teresa; Giancardo, Luca
Abstract: Measuring cognitive function is essential for characterizing brain health and tracking cognitive decline in Alzheimer's Disease and other neurodegenerative conditions. Current tools to accurately evaluate cognitive impairment typically rely on a battery of questionnaires administered during clinical visits which is essential for the acquisition of repeated measurements in longitudinal studies. Previous studies have shown that the remote data collection of passively monitored daily interaction with personal digital devices can measure motor signs in the early stages of synucleinopathies, as well as facilitate longitudinal patient assessment in the real-world scenario with high patient compliance. This was achieved by the automatic discovery of patterns in the time series of keystroke dynamics, i.e. the time required to press and release keys, by machine learning algorithms. In this work, our hypothesis is that the typing patterns generated from user-device interaction may reflect relevant features of the effects of cognitive impairment caused by neurodegeneration. We use machine learning algorithms to estimate cognitive performance through the analysis of keystroke dynamic patterns that were extracted from mechanical and touchscreen keyboard use in a dataset of cognitively normal ( n  = 39, 51% male) and cognitively impaired subjects ( n  = 38, 60% male). These algorithms are trained and evaluated using a novel framework that integrates items from multiple neuropsychological and clinical scales into cognitive subdomains to generate a more holistic representation of multifaceted clinical signs. In our results, we see that these models based on typing input achieve moderate correlations with verbal memory, non-verbal memory and executive function subdomains [Spearman's ρ between 0.54 ( P  < 0.001) and 0.42 ( P  < 0.001)] and a weak correlation with language/verbal skills [Spearman's ρ 0.30 ( P  < 0.05)]. In addition, we observe a moderate correlation between our typing-based approach and the Total Montreal Cognitive Assessment score [Spearman's ρ 0.48 ( P  < 0.001)]. Finally, we show that these machine learning models can perform better by using our subdomain framework that integrates the information from multiple neuropsychological scales as opposed to using the individual items that make up these scales. Our results support our hypothesis that typing patterns are able to reflect the effects of neurodegeneration in mild cognitive impairment and Alzheimer's disease and that this new subdomain framework both helps the development of machine learning models and improves their interpretability. Abstract : Holmes and Tripathi et al. report moderate to good correlations of typing-based machine learning models to estimate cognitive performance with the clinical subdomains of verbal memory, non-verbal memory and executive function subdomains and a fair correlation with language/verbal skills. Graphical Abstract: Graphical abstract